Wear properties of self-lubricating CrxSy/Ni coatings on 304 stainless steel by pre-placed laser cladding. (2nd December 2021) - Wang, Yijin; Liu, Mingxia; Su, Chengming; Zhang, Peng; Chi, Baosuo; Xu, Kewei; Ma, Fei
ABSTRACT: Self-lubricating NiCrBSi–Ni/MoS2 coatings are prepared on 304 stainless steel by pre-placed laser cladding, in which Ni/MoS2 is almost completely decomposed and the Cr x S y anti-friction phase is in situ generated. Meanwhile, (Cr, Fe)2 B and (Cr, Fe)7 C3 are generated from the molten pool as a result of oversaturated B and C atoms in γ-Ni and the diffusion of Fe atoms. Therefore, the composite coatings are mainly composed of γ-(Ni, Fe), (Cr, Fe)2 B, (Cr, Fe)7 C3, and Cr x S y . When compared with the substrate, the wear rate of the coatings with 20 wt-% Ni/MoS2 is reduced by 21.16%, owing to the Cr x S y lubricating phase, while it is reduced by 25.61% for the coatings with 5 wt-% Ni/MoS2, owing to blocky (Cr, Fe)2 B or (Cr, Fe)7 C3 hard phases. The wear mechanism of the coatings is adhesive wear and oxidative wear.